Synthesis and electrochemical detection of a thiazolyl-indole natural product isolated from the nosocomial pathogen Pseudomonas aeruginosa - Buzid, A.; Muimhneachain, E.; Reen, F.; Hayes, P.; Pardo, L.; Shang, F.; O'Gara, Fergal; Sperry, J.; Luong, J.; Glennon, J.; McGlacken, G. (Springer, 2016)
Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen, capable of surviving in a broad range of natural environments and quickly acquiring resistance. It is associated with hospital-acquired infections, particularly in patients with compromised immunity, and is the primary cause of morbidity and mortality in cystic fibrosis (CF) patients. P. aeruginosa is also of nosocomial importance on dairy farms and veterinary hospitals, where it is a key morbidity factor in bovine mastitis. P. aeruginosa uses a cell-cell communication system consisting of signalling molecules to coordinate bacterial secondary metabolites, biofilm formation, and virulence. Simple and sensitive methods for the detection of biomolecules as indicators of P. aeruginosa infection would be of great clinical importance. Here, we report the synthesis of the P. aeruginosa natural product, barakacin, which was recently isolated from the bovine ruminal strain ZIO. A simple and sensitive electrochemical method was used for barakacin detection using a boron-doped diamond (BDD) and glassy carbon (GC) electrodes, based on cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The influence of electrolyte pH on the peak potential and peak currents was also investigated. At pH 2.0, the peak current was linearly dependent on barakacin concentration (in the range used, 1-10 µM), with correlation coefficients greater than 0.98 on both electrodes. The detection limit (S/N?=?3) on the BDD electrode was 100-fold lower than that obtained on the GC electrode. The optimized method using the BDD electrode was extended to bovine (cow feces) and human (sputum of a CF patient) samples. Spiked barakacin was easily detected in these matrices at a limit of 0.5 and 0.05 µM, respectively. Graphical abstract Electrochemical detection of barakacin.